Controlled synthesis and synergistic effects of graphene-supported PdAu bimetallic nanoparticles with tunable catalytic properties. Issue 14 (18th March 2015) - Liu, Chang-Hai; Liu, Rui-Hua; Sun, Qi-Jun; Chang, Jian-Bing; Gao, Xu; Liu, Yang; Lee, Shuit-Tong; Kang, Zhen-Hui; Wang, Sui-Dong
Abstract : Graphene-supported bimetallic nanoparticles are promising nanocatalysts, which can show strong and tunable catalytic activity and selectivity. Abstract : Graphene-supported bimetallic nanoparticles are promising nanocatalysts, which can show strong and tunable catalytic activity and selectivity. Herein room-temperature-ionic-liquid-assisted metal sputtering is utilized to synthesize PdAu bimetallic nanoparticles on graphene with bare surface, small size, high surface density and controlled Pd-to-Au ratio. This controllable synthetic approach is green-chemistry compatible and totally free of additives and byproducts. The supported PdAu nanoparticles show excellent catalytic capabilities for both oxidation and reduction reactions, strongly dependent on the Pd-to-Au ratio. A strong correlation among catalytic performance, bimetallic composition and charge redistribution in the PdAu nanoparticles has been demonstrated. The results suggest that sufficient Au d-holes appear to be significant to the catalysis of oxidation reaction, and a metallic Pd surface is critical to the catalysis of reduction reaction. By the present method, the bimetallic combination can be tailored for distinct types of catalytic reactions.